Zirconium Trisulfide as a Promising Cathode Material for Li Primary Thermal Batteries. Issue 14 (1st January 2016) - Giagloglou, Kyriakos; Payne, Julia L.; Crouch, Christina; Gover, Richard K. B.; Connor, Paul A.; Irvine, John T. S.
Abstract : In this work ZrS3 has been synthesized by solid state reaction in a sealed quartz tube and investigated as a candidate cathode material in Li thermal batteries. The structure of ZrS3 before and after cell testing has been studied using powder X-ray diffraction. A new spinel related material, LiZr2 S4, has been identified as the product of the electrochemical process, which can be indexed to a = 10.452(8) Å cubic unit cell. The electrochemical properties of the batteries were investigated at 500°C against Li13 Si4 by galvanostatic discharge and galvanostatic intermittent titration technique (GITT). In a thermal Li cell at 500°C a single voltage plateau of 1.70 V at a current density of 11 mA/cm 2 was achieved with capacity of 357 mA h g −1 . Therefore ZrS3 material has some promise as a cathode for Li thermal batteries.